1997
DOI: 10.1007/bf02051195
|View full text |Cite
|
Sign up to set email alerts
|

Are special investigations of value in the management of patients with fecal incontinence?

Abstract: Even experienced colorectal surgeons will misdiagnose up to one-fifth of patients presenting with fecal incontinence if assessment is based on the history and physical examination alone. However surgically correctable causes of incontinence are rarely missed on clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 14 publications
1
42
0
2
Order By: Relevance
“…As stated, most studies that included more than one examiner have been in accordance with our findings (3,7,14,17,18,25) .…”
Section: This Study Has Some Limitationssupporting
confidence: 78%
See 1 more Smart Citation
“…As stated, most studies that included more than one examiner have been in accordance with our findings (3,7,14,17,18,25) .…”
Section: This Study Has Some Limitationssupporting
confidence: 78%
“…The same authors found some correlation between anal resting and squeeze tone to resting and incremental pressures (7) . Conversely, other studies have shown that DRE tone was either not related or related only to squeeze pressures (3,9,18,25) . In this study, despite its inaccuracy in assessing anatomical defects, DRE tone was correlated to sphincter function, since women with abnormal resting tone had lower resting pressures whereas women with abnormal squeeze tone also had lower incremental anal pressures than those with normal DRE.…”
Section: Resting Tone Dre Resting Pressurementioning
confidence: 92%
“…It shows electric changes during rest, contraction of muscle and during voluntary squeeze. 9 If the curve of the manometric study was flat during contraction this means there is incontinence as shown in (Figure 1) between the two vertical red lines from the second 20 to the second 90 during applying the test.…”
Section: Special Physiological Studiesmentioning
confidence: 99%
“…The causes of fecal incontinence were: sphincter defect (14), neurogenic (37), combined incontinence (10), incontinence due to diarrhea (5) and incontinence due to small rectal capacity (< 100 mL) (5). Within these groups, the largest improvement was seen in the combined incontinence group (1.8 point) (P = 0.01).…”
Section: Effect Of Treatmentmentioning
confidence: 99%
“…Most studies that mention anorectal function tests in relation to anorectal pathology limit themselves to pre-and post-treatment results. Therefore, it often remains unclear whether AFE leads to relevant findings or subsequent change of therapy [1][2][3][4][5][6][7][8][9][10] . A large multi-centre Dutch study referred to the value of AFE for outcome of physiotherapy in patients with fecal incontinence [1] .…”
Section: Introductionmentioning
confidence: 99%